La escritura de la historia en la novelística venezolana. Tres novelas, tres autores: Enrique Bernardo Núñez, Arturo Uslar Pietri y Miguel Otero Silva - Carrillo Pimentel, Margoth (La Colmena; Núm. 33 (2002), 2017)
_